Transformasi Nasional Pancasila, Kebebasan Berpendapat, dan Prioritas Pendidikan - Rozi, Ahmad Fahrul; Firlyana , Robby; Asbari, Masduki (AGUSPATI RESEARCH INSTITUTA, 2024)
National transformation is a complex and important process in the development of a country. This involves significant changes in various aspects of life, including political, economic, social, and cultural. National transformation aims to achieve progress and success in order to achieve a better development vision. In the Indonesian context, national transformation is one of the main agendas that must be faced to achieve the ideals of more advanced and sustainable development. The aim of this study is to determine and analyze efforts to achieve national transformation of Pancasila, freedom of opinion and education in Indonesia. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Mata Najwa YouTube channel entitled “Prabowo Subianto Talks Ideas | Mata Najwa” which was explained by the Minister of Defense of the Republic of Indonesia, namely Prabowo Subianto. The results of this study explain the importance of the transformation of Pancasila for the continuity of daily life, freedom of opinion in public spaces, and the absolute importance of education.